PENGARUH TINGKAT PENDIDIKAN, BUDAYA ORGANISASI, PENGALAMAN KERJA TERHADAP ETOS KERJA KARYAWAN PT. DIAN MEGA KURNIA - Wahyu Danang Setiawan; Kumara Adji Kusuma; Hasan Ubaidillah (Halu Oleo University, 2025)
This study aims to determine the Influence of Education Level, organisational culture and Work Experience on Employee Work Ethic at PT. Dian Mega Kurnia. The sample in this study with the saturated sampling method with census samples, on Employee Work at PT. Dian Mega Kurnia. The data collection technique uses a questionnaire that is distributed or distributed via Google Forms, by taking 95 respondents in the sampling of this study. The analysis technique used in this study is the testing of the measurement model (Outer Model) carried out to test indicators against variables with the results of the study showing that Education Level on Work Ethic with a t statistic value of 3,494> 1.96, then Education Level affects Work Ethic Organizational Culture on Work Ethic with a t statistic value of 2,813> 1.96, then Organizational Culture affects Work Ethic Work Experience on Work Ethic with a t statistic value of 3,768> 1.96, then Work Experience affects Work Ethic.